Improvements in the thermal, mechanical and electrical conductivity properties of a structural adhesive: A preliminary study. (February 2023) - Mabaya, M.; Aguiar, R.A.A.; Costa, H.R.M.; de Barros, A.L.F.; Reis, J.M.L.; Souza, J.P.B.
Abstract: Polymeric nanocomposites composed of an organic matrix and inorganic nanoparticles makes a useful union of the polymer functionalities, such as low weight and moldability, with the good mechanical, thermal and electrical properties of the nanofillers. The possibilities to improve mechanical or thermal properties, developing a new material, by nanoparticles, have found applications in both academia and industry. To increase the application of adhesive bonding, many researchers have developed special hybrid welding technologies to improve bonding properties. Although epoxy resins have presented the disadvantage of not being electrically conductive – as a matrix for adhesives – electrical conductivity is a necessary property for hybrid joints of adhesive and resistance spot welding techniques. In the way to promote the weldability in adhesive joints, the objective of this paper is to develop a conductive structural adhesive by adding nanoparticles in a well-established structural adhesive. The results show that multiwalled carbon nanotubes can be the desirable filler to improve the electrical conductivity of epoxy adhesives with the addition of low concentrations of nanoparticles with a formulation comprising 1.5% CNT added to the studied adhesive presenting the best results.